Development of Digital Flip Book Media "Our-World" to Increase Learning Motivation of Third Grade Students of Semarangan 1 Elementary School, Sleman - Luluk Dina Aulia Wijayanti; Arip Febrianto (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
This study aims to develop a digital flip book learning media titled “Our-World” for third grade elementary school students and to examine its feasibility, practicality, and effectiveness in improving students’ learning motivation. The research employed a Research and Development (R&D) method using the ADDIE model, which consists of analysis, design, development, implementation, and evaluation stages. The study was conducted at Semarangan 1 elementry school, Sleman. Data were collected through expert validation sheets, teacher and student response questionnaires, and learning motivation questionnaires administered before and after the use of the media. The results showed that the digital flip book media was categorized as very feasible, with a validation score of 83% from media experts and 94.44% from material experts. The practicality test results indicated very positive responses from teachers and students. Furthermore, the effectiveness test showed a significant increase in students’ learning motivation, as indicated by the Paired Sample t-test result with a significance value of 0.000 (< 0.05). The initial motivation questionnaire yielded an average score of 68.9, and the final motivation questionnaire yielded an average score of 83.68. These results represent a 14.78% increase. These findings indicate that the developed digital flip book media is feasible, practical, and effective for enhancing learning motivation in IPAS learning for third grade elementary school students. Keywords: Digital Flip Book, Learning Media, Learning Motivation